Potencialidade energética da madeira de duas espécies florestais via uso direto e através da pirólise - Rancatti, Heloisa (2012)
The present work aimed the evaluation of the energetic potential of wood and charcoal from bracatinga (Mimosa scabrella Bentham) and japanese grapes (Hovenia dulcis Thunberg). The charcoal was obtained in a laboratory by pyrolysis of wood employing combinations of three final temperature (300, 400 and 500ºC) and two heating rates (3 e 5°C / min). Was determined the properties of woods through their characterization (immediate chemical analysis and elemental, higher calorific value and lower) and later the quality parameters of charcoal by calculating the gravimetric yield and energetic in charcoal; percentage of non condensable gases and pyroligneous liquor; immediate chemical analysis and elemental, upper and lower calorific value, and friability. Based on the results obtained was concluded that: a) bracatinga and japanese grapes woods showed statistical differences only for the content of volatile materials, ash content and of nitrogen, being equal to the other parameters evaluated; b) The gravimetric and energetic yield in charcoal decreased with the increase of the final temperature of pyrolysis to the two studied species; c) The yield of the pyroligneous liquor was not affected by the final temperature and heating rate; d) The increase of final temperature reduced the content of volatile materials and increased the content of fixed carbon and ash; e) The final temperature caused alterations in the percentage of carbon, hydrogen, nitrogen, oxygen, and sulfur charcoal, while the heating rate was not significant in their elementary components; f) The calorific value increased with the increase of the final temperature for the two species; g) The yield in fixed carbon was not influenced by the final temperature and heating rate for bracatinga and it decreased with increase of the final temperature to the japanese grapes; h) The friability of the grape-of-japan charcoal was not affected by two factors studied, whereas the coal of bracatinga increased with the increase in heating rate.